Intelligent screening system for thalassemia - Nadiatun Zawiyah Supardi (School of Mechatronic Engineering, 2016)
The main scope of this study is to develop an intelligent screening system for thalassemia. In order to develop the system, various aspects are identified. These aspects consist of choosing cell images to represent each types of thalassemia, choosing the best statistical features to describe each type of thalassemia and normal RBC, predicting the dependability of extracted features based on the data distribution and choosing the best normalization, classification and classifier for the system. Nevertheless, another important aspect covered by this study is selecting the optimum number of features that best discriminate thalassemia blood cell images.